2002
DOI: 10.1097/00000542-200207000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane but Not Propofol Preserves Myocardial Function in Coronary Surgery Patients

Abstract: Sevoflurane preserved LV function after CPB with less evidence of myocardial damage in the first 36 h postoperatively. These data suggest a cardioprotective effect of sevoflurane during coronary artery surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
146
5
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(167 citation statements)
references
References 0 publications
2
146
5
11
Order By: Relevance
“…This contrasts with reports where total intravenous anesthesia with propofol and remifentanil was used for cardiac surgery. 17 Consistent with our definition of cardiac depression, we did not observe a decrease in CI across dosing groups upon emergence from CPB. This pattern was associated with a decrease in SVRI and the maintenance of LVSWI (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…This contrasts with reports where total intravenous anesthesia with propofol and remifentanil was used for cardiac surgery. 17 Consistent with our definition of cardiac depression, we did not observe a decrease in CI across dosing groups upon emergence from CPB. This pattern was associated with a decrease in SVRI and the maintenance of LVSWI (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…133 Volatile anesthetics (sevoflurane, isoflurane, and desflurane) have, in several experimental and clinical settings, been shown to protect the heart from I/R injury. [134][135][136][137] Recently, isoflurane was demonstrated to have a similar effect on the rat liver, 138 and sevoflurane, in a prospective randomized study, protected the human liver from I/R injury during liver resection. 139 It is our practice to administer volatile anesthetics at least during the last 30 min before aortic cross clamping.…”
Section: Pulmonary Carementioning
confidence: 97%
“…Sevoflurane also appears to exhibit cardioprotective effects against reperfusion injury, and this effect has been attributed to its free radical scavenging properties and the reduction of postischemic adhesion of neutrophils. 31,32 Recently, a small study comparing sevoflurane with propofol showed that sevoflurane was superior to propofol in terms of reperfusion injury and contractile function in humans, 33 although the two groups were not homogenous with respect to preoperative ejection fraction and the number of surgical techniques. In our study, in animals anesthetized with propofol, we observed lower plasma inflammatory cytokine levels, these being able to stimulate and increase neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%